Estudio del cumplimiento de normas y estándares en sitios web de instituciones públicas del cantón Bolívar. - Leones Loor, Carolina Beatriz (2014)
The study of the websites of public institutions of canton Bolívar, allowed diagnose the level of compliance with national standards and Web standards, using a mixed methodology consisting Incomplete Induction Method (section 2.4.1.1.) for determine the norms and standards to be considered for the evaluation of web portals. Consecutively, was used Complete Induction Method (section 2.4.1.2.), allowing to choose existing government entities in canton Bolívar who own website, which apply this study. Finally, was incorporated the PRIMA methodology (section 2.4.2), considering four phases: Identifying Weaknesses, included the use of questionnaires to institutions based on country regulation and Web standards, and were surveyed users of Web sites; in the phase of analysis Impact and Risk, was determined the level of agreement of responses by the Kendall coefficient (Section 4.1.4.), with the application of Web validators and analysis of Web sites, we determined that the level of compliance is high in all three institutions, however several weaknesses, such as low readability detected in certain content; in the phase Definition Countermeasures, recommendations were established, including that the design is made based on the Web standards, also post the information required by the Law, such as the organizational structure of the; finally, were presented the reports on the current status of Web sites.